Continuidades y cambios de la Matriz Sociopolítica en Chile desde la reinauguración democrática - de la Fuente, Gloria (Revista de Sociología, 2010)
The document reviews the main characteristics of the classical Sociopolitical Matrix (MSP) or State National Popular (MENP) in Chile for a large period of the twentieth century, using the approach provided by the MSP for the analysis of social transformations. It considers two central elements of the matrix, the political regime and the model of development. Later, the effect of the 1973 coup and the following dictatorship in Chile in these components of the MSP is analyzed. With this analysis in view, the author explores the patterns of continuity, change and emerging trends in Chile in those two elements, since the return of the democracy in 1990.